The Management of Children and Adolescents with Overactive Bladder Refractory to Treatment with Parasacral Transcutaneous Electrical Nerve Stimulation - Carlos Eduardo Rocha Macedo; Antônio Vitor Nascimento Martinelli Braga; Felipe Santos Marimpietri; Beatriz Paixão Argollo; Glicia Estevam de Abreu; Maria Luiza Veiga da Fonseca; Ana Aparecida Nascimento Martinelli Braga; Ubirajara Barroso Jr. (International Brazilian Journal of Urology)
ABSTRACT Background: Although parasacral TENS (pTENS) has been employed in various centers, there is a lack of studies on how children with overactive bladder (OAB) respond after failing to complete pTENS sessions. This study aimed to describe and assess treatments for OAB in children who did not respond to pTENS. Material and Methods: This retrospective case series examined patients aged 4-17 years. Patients were given subsequent treatment options, including: behavioral therapies; oxybutynin; imipramine; a combination of oxybutynin and imipramine; parasacral percutaneous electrical nerve stimulation (PENS); or a repeat course of pTENS. Outcomes were evaluated using the Dysfunctional Voiding Scoring System (DVSS) and the Visual Analogue Scale (VAS). Results: Thirty children were included, with a median age of 7 years. Patients received one or more treatments. Of these, 70% underwent monotherapy. Among them, 57% experienced complete resolution of symptoms, 28% had partial resolution and were satisfied with the results, and 14% discontinued treatment. 30% out of the whole sample continued to experience bothersome symptoms. Complete response, according to initial subsequent, was achieved in: 54% with intensified behavioral therapies, 33% with oxybutynin, and 50% with imipramine alone. The median DVSS score decreased from 7.0 to 2.0 (p=0.025), while the median VAS score increased from 80 to 100 (p<0.001). Conclusion: Children with OAB refractory to pTENS who received structured subsequent treatments showed partial response in all cases, with complete symptom resolution in half of the patients. More intensive urotherapy, medications, or repeat pTENS in combination with oxybutinin can be effective for managing this challenging condition.